Highlight on the dynamic organization of the nucleus. (2nd January 2017) - Thorpe, Stephen D.; Charpentier, Myriam
ABSTRACT: The last decade has seen rapid advances in our understanding of the proteins of the nuclear envelope, which have multiple roles including positioning the nucleus, maintaining its structural organization, and in events ranging from mitosis and meiosis to chromatin positioning and gene expression. Diverse new and stimulating results relating to nuclear organization and genome function from across kingdoms were presented in a session stream entitled "Dynamic Organization of the Nucleus" at this year's Society of Experimental Biology (SEB) meeting in Brighton, UK (July 2016). This was the first session stream run by the Nuclear Dynamics Special Interest Group, which was organized by David Evans, Katja Graumann (both Oxford Brookes University, UK) and Iris Meier (Ohio State University, USA). The session featured presentations on areas relating to nuclear organization across kingdoms including the nuclear envelope, chromatin organization, and genome function.